Quantitative comparisons of very-high-energy gamma-ray blazar flares with relativistic reconnection models - Jormanainen J.; Hovatta T.; Christie I.M.; Lindfors E.; Petropoulou M.; Liodakis I. (EDP Sciences, 2025)
The origin of extremely fast variability is one of the long-standing questions in the gamma-ray astronomy of blazars. While many models explain the slower, lower energy variability, they cannot easily account for such fast flares reaching hour-to-minute timescales. Magnetic reconnection, a process where magnetic energy is converted to the acceleration of relativistic particles in the reconnection layer, is a candidate solution to this problem. In this work, we employ state-of-the-art particle-in-cell simulations in a statistical comparison with observations of a flaring episode of a well-known blazar, Mrk 421, at a very high energy (VHE, E > 100 GeV). We tested the predictions of our model by generating simulated VHE light curves that we compared quantitatively with methods that we have developed for a precise evaluation of theoretical and observed data. With our analysis, we can constrain the parameter space of the model, such as the magnetic field strength of the unreconnected plasma, viewing angle and the reconnection layer orientation in the blazar jet. Our analysis favours parameter spaces with magnetic field strength 0.1 G, rather large viewing angles (6 − 8°), and misaligned layer angles, offering a strong candidate explanation for the Doppler crisis often observed in the jets of high synchrotron peaking blazars.